The Preparation of a AuCN/Prussian Blue Nanocube Composite through Galvanic Replacement Enhances Stability for Electrocatalysis. Issue 19 (4th July 2017) - Ren, Baiyu; Jones, Lathe A.; Oppedisano, Daniel K.; Kandjani, Ahmad Esmaielzadeh; Chen, Miao; Antolasic, Frank; Ippolito, Samuel J.; Bhargava, Suresh K.
Abstract: A stable AuCN/Prussian Blue (PB) Nanocube composite was prepared by galvanic replacement of PB cubes with HAuCl4 solution. The simple one‐step method leads to a composite with an increased surface area and pore volume, but smaller surface pore sizes than pure PB cubes. When the electrochemical detection of H2 O2 was used as a model electrocatalytic reaction, the AuCN/PB composite showed considerably improved stability. This stability is evident in a stable current response, lower background current, and improvement in both sensitivity and limit of detection compared to pure PB. This stability was attributed to the stabilisation of the surface of PB with AuCN, which prevents decomposition of the reduced form of PB during electrocatalysis. The new material shows that redox active Metal Organic Frameworks (MOFs) used for electrochemical sensing or catalysis can be tuned for surface porosity, and stabilised via galvanic replacement with a noble metal salt, leading to improved electroanalytical performance. Abstract : A new Prussian Blue (PB) composite surface‐decorated with AuCN is far more stable than the PB parent material, leading to enhanced performance for electrocatalysis, which was demonstrated through H2 O2 sensing.